Política e internet : o governo eletrônico da Prefeitura de São Paulo (2001-2006). - Tonhati, Tânia Mara Passarelli (Universidade Federal de São Carlos, 2007)
This dissertation provides a reflexion about the use of the Communication and Information Technologies (CIT s), particularly, the Internet, by São Paulo city s government. In order to achieve this, we have used, as empirical corpus, the analysis of São Paulo s electronic government politics from 2001 to 2006, we also emphasized both elements which are included in this politics: the City Hall Portal and the Digital Inclusion Plan. This way, we intend to comprehend how and in which extension this politics integrates the city s government with the actual installation demands of a new management model, which, in its turns, is defined by the Market principles. It is also important to understand how São Paulo s city government intends to enlarge citizens participation in the public management. With the aim to measure these elements, this research is based on five participation degrees, called digital democratic degrees. To reinforce this investigation, we have studied documents (such as laws, decrees, bylaws and communications), interviewed people responsible for the electronic government politics in the designated period, and we have evaluated the City Hall Portal as well as the users of the telecentres, idealized by the Digital Inclusion Plan.
Keywords: Sociologia política; Internet (Redes de computação); Governo eletrônico; Inclusão digital; Democracia; Internet; Electronic Government; Digital Democratic; São Paulo City Hall; CIENCIAS HUMANAS